Changes in salivary markers during basketball long-term and short-term training periods: a systematic review - Kamarauskas, Paulius; Conte, Daniele (Biology of Sport, 2022)
Changes in salivary markers have been largely assessed during different modalities of long-term and short-term basketball training across different basketball populations. The aim of this paper was to systematically review the literature assessing changes in salivary markers in basketball following long-term and short-term training periods. An electronic database search of articles published until October 2020 was completed in PubMed, SPORTDiscus, Scopus and Web of Science. Studies were then screened and selected using predefined selection criteria with 1080 articles identified. After removing 690 duplicates, 390 articles were included for screening, which revealed 15 articles that met the inclusion criteria. The main findings revealed no changes in testosterone (T), cortisol (C) or their ratio (T:C), while contrasting results were found in immunoglobulin A (IgA) and total protein (TP) levels across long-term periodized training periods in different basketball populations. The analysis of short-term training periods showed that strength-hypertrophy training induced higher C levels compared to a non-exercising day, one-power training and one-endurance training session in female basketball players, while no changes were evident for T and IgA. Moreover, the analysis of salivary markers in response to small-sided games (SSGs) documented a large-to-moderate increase in alpha-amylase (AA) from pre- to postSSG and inconsistent results of C and T across differently designed SSGs. The current results provide a detailed description of salivary marker changes in response to different basketball long- and short-term training periods, which can help practitioners in designing sound training programmes to optimize players’ fitness and health status across different phases of the season.